The Role of Students’ Personal Traits in Shaping Intercultural Competence in English Language Learning - Faoyan Agus Furyanto; Siti Julaihah; Lusiana Dewi Kusumayati (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
In addition to characterizing people's distinctive thought and emotion patterns, personality traits also have an impact on cultural values and interpersonal interactions. Although the relationship between personality traits and intercultural communicative competence (ICC) has been extensively studied in a variety of educational contexts, there is still a dearth of research specifically looking at this relationship among English language learners preparing for careers abroad, especially in specialized fields like aviation. The objectives of this study are to: (1) identify the personality qualities that best support students' intercultural communicative competence; and (2) ascertain which ICC components need the most improvement. Surabaya Aviation Polytechnic students were given questionnaires to complete in order to gather data using a quantitative technique. The results show that (1) most students have relatively low levels of neuroticism and high levels of conscientiousness and openness, which are bolstered by positive social qualities like extraversion and agreeableness. This combination shows a well-rounded personality profile that promotes productive learning, teamwork, and mental health in the classroom. (2) Students have established a solid foundation of intercultural competency, exhibiting noteworthy strengths in awareness and thinking but still needing to work on their practical communication abilities.